ДИСТАНЦІЙНЕ КЕРУВАННЯ ЕЛЕКТРОТЕХНІЧНИМИ ПРИСТРОЯМИ В СИСТЕМІ РЕГУЛЮВАННЯ МІКРОКЛІМАТУ - Хижняк, Т.А.; Гусєв, О.О.; Ліпінський, І.С. (Інститут електродинаміки НАН України, Київ, 2016)
The software for remote control of electrical devices that are part of microclimate control system (electric heating equipment, drives in blocks opening/closing of windows, control devices for lighting) via the Internet developed. Hardware of control systems based at 1-wire technology, executive devices which are adapted to work in this network and personal computer with specially designed web-server and web-site, which are provide a convenient interface for remote control of microclimate. References 4, figures 5.